Quantitative Research on Temporal and Spatial Distributions of Green Water on Basin Scale - Hongtao Wu; Chunyou Wu; Fanghua Hao (2008 4th International Conference on Wireless Communications, Networking and Mobile Computing, 2008)
"Green Water" was disregarded in traditional water resource researches, which has been the subject of much interest in recent years in the world. By now, most of the green water evaluation methods only focus on large scale (e.g. global scale) area, which is lack of precision. In this study, a hydrological model, SWAT (Soil and Water Assessment Tool), is introduced to quantitatively evaluate the green water at subbasin level on basin scale for the distribution study with a case study in a 1,328 km 2 river basin in Northeastern China. First, a runoff simulation model in study area is set up by SWAT after data compilation, model setup, model calibration and validation. Then the temporal and spatial distributions of the green water are worked out based on the outputs of the runoff model with the help of ArcGIS9.1. Finally, the distribution laws are found out, by which some useful management suggestions are raised. All the results show that this method is efficient for quantitative research on temporal and spatial distributions of "Green Water" on small scale, which can benefit the normal green water study and decision making for planning and management of water resources and ecosystem services a lot.